How to Live as a Muslim (Hayatul Muslimeen) - Ashraf Ali Thanvi (Rawalpindi Service Book Center, 2003)
Maulana Ashraf Ali Thanvi (ra) was a man, one of those of whom the Prophet (Sallallahu Alyhi wa Sallam) said that Allah will send one at the beginning of every century. He has written this book "Hayatul Muslimeen" in urdu. There could not have been a better time for this book to come to light. The Muslim Ummah is in a dismal shape. Their way of life has almost no comparison to the Islam taught by the Prophet (Sallallahu Ahyhi wa Sallam). Muslims have fallen into an abyss. The book endeavors to guide how to set the Ummah on the correct course on the basis suggested by Allah'a messengers (Sallallahu Alyhi wa Sallam). It draws much on the Quran and the Ahadith.
Keywords: Islam--Customs and Practices